Design sensitivity analysis of three-storey reinforced concrete moment resisting frame structures using performance-based seismic engineering - Sawali, John Paul M.; Pacheco, Benito M.; Suiza, Raniel M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study aims to quantify the sensitivity of earthquake-sensitive components of a three-storey reinforced concrete moment resisting frame structure in Metro Manila to the seismic hazard by observing engineering demand parameters. Performance-based design framework was adapted in this study to account uncertainties from the seismic hazard and building response. The methodology implemented involves the variation of column dimensions, beam dimensions, and floor area holding others constant. Fragility, vulnerability and risk curves are derived from the results of nonlinear static analysis and capacity spectrum method. Maximum inter-storey drift was determined from the building capacity curve using scaled base shear. For maximum inter-storey drift, the sensitivity index of the column dimension, beam dimension and floor area are 50%, 36%, and 32% respectively that remains constant across peak ground acceleration. For the damage index, the sensitivity index is inversely proportional to the peak ground acceleration. The study can be applied to determine the sensitivity of building components of other building types in Metro Manila.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake resistant design; Buildings -- Earthquake effects